Manajemen Pendidikan Anak Usia Dini Pada RA Annur Babalan - Armanila Armanila; Alya Sabrina Ramdhani Hsb; Ijar Salna; Lu’lu Rahmadanti; Nur Saadah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to describe the management of early childhood education at RA Annur Babalan. This research uses a qualitative approach and is descriptive in nature. The selection of research subjects was carried out using purposive sampling technique. Research subjects are managers, educators, students and parents. Data was collected through observation, interviews and documentation. Checking the validity of the data is carried out through diligent observation, participation and adequacy of references. The research results show that the RA Annur Babalan management program has been prepared in accordance with the institution's vision and mission by carrying out management functions including; implementation, supervision and guidance. Managers as leaders in carrying out management functions place great emphasis on cooperation based on sincerity, enthusiasm and high loyalty. Planning is carried out with strategic planning, preparing learning plans ranging from yearly, semester, monthly, weekly to daily. Organizing is carried out by coordinating tasks, opportunities, experiences and insights with open communication, holding regular meetings to discuss efforts to improve performance. Supervision is carried out by direct observation, through supervision, regular meetings with educators. Collaboration ends with parents, through monthly meetings (parenting), and partners related to RA. Assessment and evaluation is carried out by giving assignments, observations, daily notes, anecdotes, performance, work results and educational visits.